Dental Health Evaluation of Children in Kosovo - Begzati, Agim; Meqa, Kastriot; Siegenthaler, David; Berisha, Merita; Mautsch, Walter (European Journal of Dentistry, 2011)
Objectives: The aim of this study was to assess caries prevalence of preschool and school children in Kosovo. Methods: The assessment, which was carried out between 2002 and 2005, included measurements of early childhood caries, deft and DMFT. Results: In total, 1,237 preschool and 2,556 school children were examined. The mean deft of preschool children was 5.9, and the mean DMFT of school children aged 12 was 5.8. The caries prevalence for 2- to 6-year-old preschool children was 91.2%, and the prevalence for 7- to 14-yearold school children was 94.4%. The prevalence of early childhood caries was 17.6%, with a mean deft of 10.6. Conclusions: All data assessed showed the very poor oral health status of children in Kosovo. Interviews with children and teachers indicated poor knowledge regarding oral health. Significant measures must be taken to improve this situation. (Eur J Dent 2011;5:32-39)
Keywords: Caries prevalence; deft/DMFT; Preschool children; School children; Prevention